المزيج الموسع للتسويق السياحي ودوره في تحسين الصورة السياحية للدولة - تامه ،جاسم (جامعة الوادي University of Eloued, 2025)
تهدف هذه الورقة البحثية إلى تسليط الضوء على التسويق السياحي ومزيجه التسويقي، وكذلك العوامل المتدخلة في العمليات التسويقية السياحية، ومعرفة الدور الذي يلعبه التسويق السياحي في تحسين الصورة السياحية للدولة القطرية التي كانت محل دراستنا. وخلصت هذه الدراسة إلى أن تطبيق التسويق السياحي بمختلف عملياته التسويقية يلعب الدور البارز والأكبر في تحسين الصورة السياحية للدولة القطرية، وقد تحقق ذلك من خلال زيادة عدد الوافدين السياحيين الدوليين مع تسجيل معدلات نمو إيجابية من سنة إلى أخرى، كما أن الإيرادات السياحية للدولة القطرية في نمو مستمر ومن المتوقع أن تصل إلى أرقام قياسية في هذه الفترة، إضافة إلى ذلك وجدنا أن هناك تزايد في نسبة الإشغال الناتجة عن القطاع السياحي في مختلف مرافقه ومنشآته، سواء على القطاع الخاص أو العام. This research paper aims to shed light on tourism marketing and its marketing mix, As well as the factors involved in touism marketing operations, And to know the role that tourism marketing plays in improving the tourism image of the Qatari statethat was the subject of our study. This study concluded that the application f tourism marketing in its various marketing operations plays the most prominent and largest role in improving the tourism image of the Qatari state. This was achieved by increasing the number of international tourist arrivals while recording positive growth rates from year to year. Also, The tourism revenues of the Qatari state are constantly growing and are expected to reach record numbers during this period, In addition, we found that there is an increase in the occupancy rate resulting from the tourism sector in its various facilities and establishments, whether in the private or public sector.
The expanded mix of tourism marketing and its role in improving the tourism image of the country –Qatar asa model-
Keywords: Tourism marketing; Marketing mix; Economic development; Tourism Image; tourism development; تسويق سياحي; مزيج تسويقي سياحي; تنمية اقتصادية